Pengaruh Media Pembelajaran Video Animasi terhadap Hasil Belajar IPA Kelas III SD Negeri Larangan 09 - Sevira Feliana Yusuf; Rizki Zuliani (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The purpose of this study was to find out the difference between student learning outcomes by using animated video media with image media or not using animated videos, by conducting experimental research that is nenoquivalent control group design. The study sample of SDN Larangan 09 kela IIIA amounted to 25 students (control class) and class IIIB amounted to 25 students (experimental classes) resulted from the calculation that the average pretest and postest grades of control classes amounted to 5.42 and 5.42. While the results of the calculation of the pretest and postest experimental class average values were 5.26 and 6.82. So it can be concluded from the research that the use of animated video media significantly affects the learning outcomes of students of class III SDN Larangan 09 Tangerang.